The Campos’ Mask and the masks of Campos by sociological perspective of Erving Goffman - De Paula, Marcelo Ferraz; Fagundes, Kelly Loreto (Revista Desassossego, 2021)
According to Goffman (1975), the social life is a continuous representation, which requires different roles from us in different contexts. Fernando Pessoa vigorously explores these roles in the construction and deconstruction of his poetic authorship: he creates scenarios, poets-heteronyms and his own events of sensation and pretense. Based on this observation, we propose a reading of poems by Álvaro de Campos, a heteronym in which this resource is more explored. As a Pessoa mask, this heteronym, in turn, also masks and unmasks itself in poetry. Resuming canonical studies about the heteronomy, we intend to contribute to these readings by dialoguing with the sociological perspective of Goffman (1975), emphasizing the importance of the mask as a problematization of the authorial instance in Fernando Pessoa.